ANALISIS KALIMAT TUNGGAL CERPEN RUANGSASTRA.COM “PESAN DARI SEORANG YANG BERNAMA PRESIDEN” KARYA MUHAMMAD RAMADHAN BATUBARA - Muhammad Prasetyo Nugroho; Dilla Amalia Putri; Dian Lestari; Wanda Hamidah; Iis Lisnawati; Nibia Zahra Pamela (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This study aims to analyze simple sentences in the short story entitled Pesan dari Seorang yang Bernama Presiden by Muhammad Ramadhan Batubara, published on the online platform ruangsastra.com. The main focus of this research is to identify the types of simple sentences used in the short story and to analyze their syntactic structures based on the functional categories of subject, predicate, object, complement, and adverbial. The method employed in this study is descriptive qualitative, using techniques to identify sentences that meet the criteria of simple sentences. The results of the research show that the short story features simple sentences with verbal predicates, nominal predicates, and adjectival phrase predicates, exhibiting structural variations that reflect the author's distinctive narrative style. These simple sentences function not only to convey the plot but also to depict the psychological atmosphere of the characters and to build the paradoxical nuance surrounding the mysterious figure of the